Association between family assessment tools and depression in adolescents: a cross-sectional - Putri Rizki Amalia Badri; Resy Asmalia; Dientyah Nur Anggina; Ardi Artanto; Erwin Maulana; Ahmad Ghifari; Puput Nafdyla Murti (Berita Kedokteran Masyarakat, 2026)
Purpose: Adolescents are very vulnerable to depression because adolescence is a period of psychological development. Research on family function in adolescents experiencing depression is still limited. This study aims to determine the association of family assessment tools with depression in adolescents. Methods: This study was an observational, cross-sectional analysis conducted from October to December 2024. The population of this study was all high school students at SMAN 4 Palembang, and the sample was all 3rd-grade students who met the inclusion and exclusion criteria. A total of 177 respondents were included. The independent variable studied was the family assessment tools, and the dependent variable was depression. The Family function examination is assessed using the APGAR score, which consists of adaptation, partnership, growth, affection, and resolve. In contrast, the SCREEM consists of social, cultural, religious, economic, educational, and medical. Adolescent mental health was measured using the Children's Depression Inventory Questionnaire. The data were then analyzed using the chi-square test, and the Fisher test if the chi-square test did not meet its assumptions. Results: There were significant relationships between APGAR score (p-value=0.000), social (p-value=0.001), culture (p-value=0.003), religion (p-value=0.000), and education (p-value=0.003) and adolescent depression. There is no relationship between the economy (p-value 0.387) and access to health (p-value=0.797) in depression in adolescents. Conclusion: APGAR scores can be integrated into family folders within health services to facilitate practitioners' involvement of families in depression management. Families are expected to play a greater role, especially in the social, cultural, religious, and educational spheres.